Diit Rendah Karbohidrat dan Puasa Intermitten terhadap Tekanan Darah pada Penderita Hipertensi - Wahadi, Wahadi; Nurachmah, Elly; Maria, Riri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of a low carbohydrate diet and intermittent fasting on blood pressure in hypertension sufferers. The research method used literature searches published in electronic databases, namely PubMed, Google Scholar, Scopus, and ScienceDirect, from 2013 to 2023, using the PRISMA method. Research shows that both can reduce blood pressure, especially systolic blood pressure. In conclusion, further research needs to be carried out to look specifically at the impact of a low-carbohydrate, high-fat diet and intermittent fasting on blood pressure in people with hypertension. Keywords: Low Carbohydrate Diet, Hypertension, Intermittent Fasting, Blood Pressure